Prospero-related homeobox 1 (Prox1) at the crossroads of diverse pathways during adult neural fate specification - Stergiopoulos, Athanasios; Elkouris, Maximilianos; Politis, Panagiotis K. (Frontiers in Cellular Neuroscience, 2015)
Over the last decades, adult neurogenesis in the central nervous system (CNS) has emerged as a fundamental process underlying physiology and disease. Recent evidence indicates that the homeobox transcription factor Prox1 is a critical intrinsic regulator of neurogenesis in the embryonic CNS and adult dentate gyrus (DG) of the hippocampus, acting in multiple ways and instructed by extrinsic cues and intrinsic factors. In the embryonic CNS, Prox1 is mechanistically involved in the regulation of proliferation versus differentiation decisions of NSCs, promoting cell cycle exit and neuronal differentiation, while inhibits astrogliogenesis. During the complex differentiation events in adult hippocampal neurogenesis, Prox1 is required for maintenance of intermediate progenitors (IPs), differentiation and maturation of glutamatergic interneurons, as well as specification of DG cell identity over CA3 pyramidal fate. The mechanism by which Prox1 exerts multiple functions involves distinct signaling pathways currently not fully highlighted. In this mini-review, we thoroughly discuss the Prox1-dependent phenotypes and molecular pathways in adult neurogenesis in relation to different upstream signaling cues and cell fate determinants. In addition, we discuss the possibility that Prox1 may act as a cross-talk point between diverse signaling cascades to achieve specific outcomes during adult neurogenesis.